Climate change and the future of Seattle - Dierwechter, Yonn (Anthem Press, 2021)
Seattle is one of the most politically progressive and economically dynamic cities in the contemporary United States, popularly known as the 'Emerald City' for its natural setting and environmental politics. This book explores a range of political, policy, and project efforts in Seattle and the wider region to mitigate and adapt to the formidable reality of global climate change. Developing a framework suggested originally by the Urban Climate Change Research Network, the book's core analysis considers both tantalizing progress and tangible problems in Seattle's climate action initiatives so far. The narrative explores how Seattle is integrating carbon mitigation with adaptation; advancing climate action networks; co-generating risk information; coordinating disaster risk reduction with climate change adaptation; and, most importantly, focusing on historically and geographically disadvantaged populations.
Title from publisher's bibliographic system (viewed on 22 Feb 2022)
Introduction : changing Seattle -- Background : Seattle's green development story -- Current situation : building a "climate-friendly" city in an unsustainable world -- The future : climate change, social vulnerabilities, and the transformational agenda -- Conclusion : Seattle's lessons
Keywords: Climatic changes / Washington (State) / Seattle; Seattle (Wash.) / Environmental conditions